If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + (-9) = f + -4 2 + -9 = f + -4 Combine like terms: 2 + -9 = -7 -7 = f + -4 Reorder the terms: -7 = -4 + f Solving -7 = -4 + f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-1f' to each side of the equation. -7 + -1f = -4 + f + -1f Combine like terms: f + -1f = 0 -7 + -1f = -4 + 0 -7 + -1f = -4 Add '7' to each side of the equation. -7 + 7 + -1f = -4 + 7 Combine like terms: -7 + 7 = 0 0 + -1f = -4 + 7 -1f = -4 + 7 Combine like terms: -4 + 7 = 3 -1f = 3 Divide each side by '-1'. f = -3 Simplifying f = -3
| 2mp+3np+2mr+3nr= | | 3n-4+6n+2=6+4n+2 | | (-5)-(-8)=g+7 | | 4x+4=19-x | | (-37)=c+(-14) | | 6a-2-4a=3a+4+5a | | 0=-5n-2n-2n | | (-5)=b+(-11) | | -8x^2-8x+160=0 | | A-5=(-8) | | 3x*26= | | 6(x-1)+2=6x-2 | | -7y=-10-8y | | 0=-4.9t^2+.686t | | J+(-3)=4 | | 7j+4=5j | | -5x-15=-20 | | 9y=9+10y | | -12+8+5=36 | | 2x+34x^2-322=0 | | 3+(-7)=f-3 | | 3y+9-8y+6-6=-5y-12 | | -12+3x=-6 | | 9n=-117 | | 3x+9-8x+6-6=-5x-12 | | 3+(-7)=4 | | -0.9+z=0.075 | | 69=3u | | 0.06x+0.02(7-x)= | | 6p+4= | | 8-3=3x-2-8x | | 4+e=8+(-2) |